(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to identify the critical thinking skills of male and female faculty members of science faculties, by answering the following question: “What are the critical thinking skills possessed by male and female faculty members of science faculties? The method used was the descriptive one. The current research community represented the teaching and teaching of science faculties for the departments (chemistry, physics and life sciences) who are in charge of the college for the academic year 2021/2022, and the research sample was represented by the College of Science / Al-Mustansiriya University, and the number of male and female teachers reached The faculty for all departments is ( ) teaching and teaching. As for the number of male and female teachers of the department (chemistry, physics and life sciences), it reached ( ) teaching and teaching. To achieve the goal of the research, a test for critical thinking skills was prepared and its paragraphs reached (40) paragraphs distributed over five areas as shown in the body of the research In the third chapter, which is (Assumptions, Interpretation, Evaluation of Arguments, Deduction, Conclusion), the validity of the tool was verified by adopting 80% of the arbitrators’ acceptance. The tool’s stability was also verified by applying the Keoder-Richardson equation 20, and after applying the search and data extraction tool. The results showed that (teachers of science colleges have critical thinking skills, but at a slightly above average rate). In the light of these results, the researcher developed a set of appropriate recommendations, and suggested conducting subsequent research to complete this research and designing programs to develop critical thinking among male and female teachers, whether in the faculties of science or the rest of the faculties.